A Proposed Ad Campaign Plan for Arce Dairy Ice Cream - Arino, Christine Diane C.; Dema-ala, Crisant S. and Meily, Myra Joy R. 4 0 16; 5
u
Thesis: (Bachelor of Mass Communication)- Pamantasan ng Lungsod ng Maynila, 2004.
Keywords: 2 -- 0; 6; 20; 20; 2